Developing and Validating the Teacher Rating Scale of Learning Interest for Kindergarteners - Wu, Chung Chin (Frontiers in Psychology, 2022)
Studies have investigated learning interest based on either 2- or 4-factor theoretical framework. Empirical studies showed supportive evidence only toward the 2-factor learning interest model, but it was primarily demonstrated above the secondary level. It is unclear whether the dimensionality of the learning interest of kindergarteners is consistent with those studies conducted above the secondary level due to the absence of an instrument for measuring kindergarteners' learning interests. An effective and efficient learning interest scale was developed and validated for teachers' use to rate kindergarteners to provide useful information for improving teaching and learning in practice. A total of 132 5-year-old kindergarteners were rated by 5 teachers in the formal study. The results clearly showed: (1) the developed teacher rating scale of learning interest was valid for understanding kindergarteners' learning interests and was equally suitable for boys and girls. (2) The 2-factor learning interest model was the best theoretical viewpoint for understanding kindergarteners' learning interests across gender. The implications for learning interest research and practice are also discussed.